Synthesis of β-Substituted Chalcones from Phenones via Conjugated Nucleophilic Substitution of Propargylic Alcohols - Halima, Taoufik Ben; Chapdelaine, Daniel (Synlett, 2012)
Phenones can be efficiently transformed into β-substituted chalcones in a two-step process. First, propargylic alcohols were obtained by addition of ethoxyacetylene anion to aromatic ketones. Activation of the propargylic alcohols using a catalytic amount of acid in the presence of an electron-rich aromatic ketone affords the title enones in moderate to good yields.
Keywords: electrophilic aromatic substitution; ketones; olefination; propargylic alcohols; chalcones